Carlsberg’s reputation as an influencing factor between consumer attitude towards corporate social responbility and brand acceptance - Mohd Hasan, Nurul Ain; Kumar, Shammanee; Chan, Tak Jie; Costa, Feroz De (Human Resource Management Academic Research Society, 2022)
Corporate social responsibility (CSR) initiatives which are carried out by an organization is one of the most powerful tools towards engaging with the public. Through carrying out such numerous social responsibility initiatives, the organization proofs to society that it is not only focused towards a profit-oriented organization but is aware of its responsibility towards the development and effect on society as well as the environment. CSR management is always a vital matter for the corporate world. Most multinationals invest millions in managing CSR initiatives to meet corporate social performance in their country of origin and in other countries in which they operate. This study gives a closer look towards corporate reputation as a factor that influences Malaysian consumers’ attitude when measuring CSR initiatives of a multinational corporation and brand acceptance. The study uses techniques of quantitative analysis and offers important insights into developing effective strategies to enhance the credibility of companies through their CSR initiatives by looking closely towards corporate reputation as a mediating factor. Focusing on results analysing our Malaysian community’s perceived attitude towards CSR and how their attitude can impact the alcohol industry’s commitment towards restoring their social obligation towards maintaining the level of negative impact on corporate reputation and brand acceptance. As CSR initiatives are important to an organization but because they affect the underlying intangible assets such as corporate reputation, identity and image thus the paper further looks into the actual acceptance level of the Malaysian consumers towards CSR initiatives by the alcohol industry.